Tetramethylpyrazine inhibits ferroptosis in spinal cord injury by regulating iron metabolism through the NRF2/ARE pathway - Tao, Jingwei; Zhou, Jingya; Zhu, Hanjie; Xu, Lin; Yang, Jizhou; Mu, Xiaohong; Fan, Xiao (Frontiers in Pharmacology, 2024)
Background: Tetramethylpyrazine (TMP) is a natural alkaloid compound with antioxidant and neuroprotective effects. We hypothesized that TMP could exert neuroprotective effects by inhibiting ferroptosis through modulating iron metabolism, but its mechanism is unclear. Through in vivo and in vitro experiments, we have explored how TMP can regulate neurons' iron metabolism through the NRF2/ARE pathway to Inhibit ferroptosis. Methods: In the in vivo experiment, the effects of TMP on nerve function and secondary spinal cord injury were observed through behavioral tests and morphology staining. Transmission electron microscopy, molecular biology tests and immunofluorescence staining were used to investigate the role of TMP in the regulation of iron metabolism and ferroptosis through the Nrf2/ARE pathway. Using in vitro experiments to investigate the mechanism of TMP in inhibiting ferroptosis through the Nrf2/ARE pathway. Results: Firstly, through in vivo experiments, we found that TMP improves motor function of rats with spinal cord injury, reduces spinal cord tissue damage and nerve cell death caused by secondary injury. Moreover, neuronal death and the formation of spinal cord cavities are inhibited by TMP. By regulating lipid peroxidation, TMP can inhibit mitochondrial damage and reduce ROS accumulation. Our study also demonstrated that TMP regulates iron metabolism through the NRF2/ARE pathway to inhibit ferroptosis and repair spinal cord injury. To further explore the regulatory mechanisms of TMP we down-regulating Nrf2 expression in subsequent in vitro experiments. We find that a key ferroptosis pathway, lipid peroxidation, can be regulated by TMP. Additionally, TMP inhibits iron overload-mediated ferroptosis by increasing Nrf2 transcriptional activity. Conclusion: A regulatory effect of TMP on the NRF2/ARE pathway was found in both in vitro and in vivo experiments. It promotes the transcription and translation of iron metabolizing and antioxidant molecules. Our study explored the inhibitory effect of TMP on ferroptosis from the iron metabolism pathway and provided new ideas for the treatment of SCI.